Growth of a Single Bubble Due to Super-Saturation: Comparison of Correlation-Based Modelling with CFD Simulation - Johannes Manthey; Wei Ding; Hossein Mehdipour; Montadhar Guesmi; Simon Unz; Uwe Hampel; Michael Beckmann (ChemEngineering)
This paper investigates and assesses the potential applicability of global mass transfer coefficients derived from large-scale experiments to the bubble growth of a single bubble in a super-saturated flow <semantics>(σ=9)</semantics>. Therefore, it presents, for a specific flow velocity <semantics>(u=1<mstyle scriptlevel="0" displaystyle="true">ms</mstyle>, Re=10,678)</semantics>, a comparison between correlation-based modelling and 3D Large Eddy Simulation–Volume of Fluid (LES-VOF) Computational Fluid Dynamics (CFD) simulations (minimum cell size of 10 µm, Δt = 10 µs). After the verification of the CFD with pool nucleation bubbles, two cases are regarded: (1) the bubble flowing in the bulk and (2) a bubble on a wall with a crossflow. The correlation-based modelling results in a nearly linear relationship between bubble radius and time; meanwhile, theoretically, the self-similarity rule offers <semantics>r~Bt0.5</semantics>. The Avdeev correlation gives the best agreement with the CFD simulation for a bubble in the flow bulk (case 1), while the laminar approach for calculation of the exposure time of the penetration theory shows good agreement with the CFD simulation for the bubble growth at the wall (case 2). This preliminary study provides the first quantitative validation of global mass transfer coefficient correlations at the single-bubble scale, suggesting that computationally intensive CFD simulations may be omitted for rapid estimations. Future work will extend the analysis to a wider range of flow velocities and bubble diameters to further validate these findings.